The Effect of Education and Job Training on Increasing Employee Competence at the Immigration Office Class 1 TPI Palembang City - M Reza Vahlevi; Luis Marnisah; M Kurniawan DP (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effectS of education and job training on improving employees' competence at the Immigration Office Class 1 TPI Palembang. The sample was selected using the saturated sample technique. Data of 70 respondents were collected through observation and questionnaires. This study implemented the multiple linear regression method to analyze data. The results evince that partially each job education and training has a significant effect on increasing employees' competence. Likewise, simultaneously education and job training have a significant effect on increasing employees' competence. The insight can benefit the Immigration Office Class 1 TPI Palembang. To improve employees' competence, the leaders of this government institution should apply the factors of education and job training.